A new formula for selecting the size of cuffed endotracheal tubes in pediatric patients - Ji Yeon Kwon; Ki Hwa Lee; Sang Eun Lee; Yong Han Kim; Sung Hyun Shin (Bali Journal of Anesthesiology, 2023)
Background: Choosing an appropriate endotracheal tube size during the first attempt is crucial for avoiding unnecessary reintubation. Previous studies on endotracheal tube size in children focused on uncuffed tubes. Following recent studies on pediatric airway anatomy, cuffed endotracheal tubes are increasingly utilized in children. The objective of our study was to develop a new formula for selecting the correctly sized cuffed endotracheal tube for pediatric patients. Materials and Methods: We examined the electronic anesthetic records of 465 pediatric patients who received elective ophthalmic surgery between January 2011 and December 2018. Multiple linear regression was used to identify potential predictors of cuffed endotracheal size among age, weight, height, body mass index, and the presence of underweight, overweight, and obesity. We used repeated-measures ANOVA to assess the difference between the actual and calculated sizes of the endotracheal tube. Results: The derived formula is as follows: Predicted endotracheal tube size (mm) = 3.7 + 0.1 × age (years) + 0.02 × weight (kg) + 0.1 × presence of overweight (0: negative, 1: positive). The coefficient of determination (R2) for the total population was 0.685 and was higher in the overweight group (R2 = 0.763). When compared with the three conventional age-based formulas (Cole’s, Khine’s, and Duracher’s formula), the difference between the actual endotracheal tube size and the endotracheal tube size calculated using Duracher’s formula was the smallest. Conclusions: In choosing the appropriate size of a cuffed endotracheal tube in children, age and body size should be considered.